MiRNA Polymorphisms and Cancer Prognosis: A Systematic Review and Meta-Analysis - Ding, Han-xi; Lv, Zhi; Yuan, Yuan; Xu, Qian (Frontiers in Oncology, 2018)
Background: Accumulating studies have focused on the relationship between miRNAs polymorphisms and cancer prognosis. However, the results are conflicting and unconvincing. This systematic review and meta-analysis was conducted to explore the relationship between miRNAs polymorphisms and cancer prognosis, aiming to seek for markers with cancer prognostic function. Methods: Hazard ratio of overall survival, disease-free survival and recurrence-free survival were calculated to evaluate the association between miRNAs polymorphisms and cancer prognosis by using Stata software 11.0. Results: We systematically reviewed the association of 17 miRNAs SNPs with cancer prognosis including 24721 samples. It was shown that 6 miRNAs SNPs (miR-608 rs4919510, miR-492 rs2289030, miR-378 rs1076064, miR-499 rs4919510, miR-149 rs2292832, miR-196a2 rs11614913) were associated with better cancer overall survival (OS) while let-7i rs10877887 was associated with poor OS; the homozygous and heterozygote genotype of miR-423 were related to poor cancer relapse-free survival (RFS) when compared with the wild genotype; miR-146 rs2910164 was linked to favorable cancer disease-free survival (DFS) while miR-196a2 rs11614913 was associated with poor DFS. Conclusions: In summary, let-7i rs10877887, miR-608 rs4919510, miR-492 rs2289030, miR-378 rs1076064, miR-423 rs6505162, miR-499 rs4919510, miR-149 rs2292832, miR-146 rs2910164 and miR-196a2 rs11614913 might serve as potential biomarkers for cancer prognosis.